Identification of Intelligence Requirements of Military Surveillance for a WSN Framework and Design of a Situation Aware Selective Resource Use Algorithm - S. Deepak Raj; H.S. Ramesh Babu (Revue d intelligence artificielle, 2022)
Protecting or safeguarding the place we live in is a basic activity of life. This is also observable in animals. Identifying a suitable place to build a nest or create a cozy home is a primary requirement of carefree living. Once such a place is identified and selected, a lot of effort and planning goes into making it comfortable. From then onwards begins the constant task of safeguarding the place of domicile. Protecting a place involves keeping a constant lookout for disruptive elements, invasion or attacks. The term corresponding to this activity is surveillance. Surveillance when extended to a city, a state, a nation and then to continents will perform the same functionality of enabling protection against attacks but at a larger scale. Unlike in case of a bird, animal or a family unit, such surveillance requires dedicated infrastructure. Usually such a large-scale surveillance infrastructure is designed, implemented and maintained by a dedicated military. Increase in organized crime and acts of terrorism have made military surveillance evermore important and an indispensable requirement of safety. In addition to attacks by men or manmade agents, natural calamities and disasters also require surveillance on an equally large scale. Surveillance which was historically centralized in deployment and investigative in essence needs to change. Existing surveillance and sensor infrastructure can be further used to gather intelligence. Aim of this work is to identify intelligence requirements of military surveillance for a WSN framework. We have designed and implemented an algorithm to compute the area under attack, communicated nearest neighbor nodes to carry out surveillance under attack. The proposed algorithm achieves situation aware selective use of sensor infrastructure.